Green Hills of Magic : West Virginia Folktales from Europe - Musick, Ruth Ann (Book collections on Project MUSE., 1970)
In the early years of this century, miners from nearly every country in Europe and Asia Minor migrated to West Virginia to seek employment in its great collieries. With them they brought many folktales and legends of then homelands. Ruth Ann Musick has collected some of the best and most representative of these stories -- never before published in book form -- in The Green Hills of Magic. In many instances, these tales were first related in family circles in the native languages of the tellers, later to be translated by their younger English-speaking descendants.